Suria Bakery & Confectionary / Nurul Asmaq Junit ... [et al.] - Junit, Nurul Asmaq; Nik Omar, Nik Nor Azlina; Zakaria, Mastini; Mohamed, Nurbaitin Nadiah; Md.Shariff, Sakini (Faculty of Information Management, 2003)
Our bakety name is Suria Bakery and Confectionary. We choose this name because it is easy to remember and different from other bakeries name, usually that name concern with bakeries like Madelline Bakery, La Bohemea Bakery and Baker Bakery. So, we here our bakery name is really different between the other bakery.